2014
DOI: 10.4103/2141-9248.144930
|View full text |Cite
|
Sign up to set email alerts
|

Unusual complications of incisional hernia

Abstract: Incisional hernia represents a breakdown or loss of continuity of a fascial closure. These hernias are of particular concern not only for the high recurrence rates among them but also for the challenges that follow their repair. It is known to occur in 11-23% of laparotomies. This paper presents two unusual complications of incisional hernia managed by the authors. One ruptured incisional hernia with evisceration of gut and a case of incarcerated gravid uterus in a woman in labour. The case records of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
0
11
0
6
Order By: Relevance
“…5,8,9 The emergency nature of the surgeries, with a high incidence of infection following the surgery, and the experience of the surgeons who performed the surgeries have been implicated as being responsible for the high number of laparotomies and cesarean sections resulting in incisional hernias. 4,5,6 Incisional hernias can present almost soon after the primary surgery or several years after. 4,5,10 The two cases reported here did not seek medical advice many years after the primary surgery, even though the swellings were noticed about a year after the primary surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,8,9 The emergency nature of the surgeries, with a high incidence of infection following the surgery, and the experience of the surgeons who performed the surgeries have been implicated as being responsible for the high number of laparotomies and cesarean sections resulting in incisional hernias. 4,5,6 Incisional hernias can present almost soon after the primary surgery or several years after. 4,5,10 The two cases reported here did not seek medical advice many years after the primary surgery, even though the swellings were noticed about a year after the primary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several authorities have reported that patients with incisional hernias only seek surgical repair because of physical discomfort or complications. 4,5,6,7,9 In sub-Saharan Africa, delayed presentation by patients with post-surgical incisional hernia is traceable to a number of varied factors. Ayandipo 11 and colleagues, working in Ibadan, southwestern Nigeria, implicated low socioeconomic status and very inadequate privately funded health care financing as being responsible for delayed presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bdominal incisional hernia is a relatively common surgical disease, with an estimated incidence of around 15-20% of all laparotomies 1 . Without treatment, it tends to increase progressively and complicate with incarceration 2,3 , obstruction, strangulation 4 , deviation of the lumbar spine with low back pain, skin ulcer, skin infection, hernia rupture 2 , loss of domain 5 , muscle changes 6 , circulatory changes 6 , respiratory failure 7 , and tends to worsen patients' quality of life 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Incisional hernia is a common complication following abdominal surgery, occurring in 10 to 20% of cases after laparotomy, but may also occur following laparoscopy [1] . The potential gravity of their typical complications such as strangulation, and atypical ones, such as evisceration, gravid visceral incarceration [2] justifies elective surgical management.…”
Section: Introductionmentioning
confidence: 99%